Dynamics of endogenous intoxication in combination with insulin resistance and excretory pancreatic insufficiency under the influence of various treatment complexes - Medvid , Ihor; Babinets , Liliya (The Ukrainian Scientific Medical Youth Journal, 2025)
In type 2 diabetes mellitus, a connection has been established between markers of inflammation, endogenous intoxication and the functional activity of pancreatic β-cells. A significant increase in endogenous intoxication due to the inflammatory process in the pancreatic tissue impairing its functions, including excretory. The aim was to assess the severity of endogenous intoxication in the presence of comorbidity of type 2 diabetes mellitus and excretory pancreatic insufficiency, to verify the feasibility of enhancing conventional treatment with the drug phenibut and acupressure techniques. 45 people with a combination of type 2 diabetes mellitus and excretory pancreatic insufficiency underwent several assessments of the severity of endogenous intoxication. Levels of medium-mass molecules with maximum absorption at wavelengths of 254 nm and 280 nm, and the sorption capacity of erythrocytes were determined. The study group was divided into subgroups according to the treatment method: standardized therapy, additional inclusion of phenibut, and strengthening the drug complex with acupressure courses. The violation of the processes of maintaining homeostasis and the increase in endogenous intoxication in the studied group is indicated by a significant excess of the control values ​​of the indicators by 1.7-2.1 times. A decrease in endogenous intoxication indicators (on average by 9.14 %) was detected during standardized therapy. However, in the sixth month, a significant repeated increase in the above indicators was observed. Additional use of phenibut had a more significant effect on the manifestations of endogenous intoxication by an average of 27.70 %. The positive dynamics were still evident when repeating the laboratory test after six months. The combination of conventional treatment, use of phenibut and undergoing a course of acupressure during the first month caused the most pronounced correction of endogenous intoxication – on average by 42.44 %. No significant dynamics of endogenous intoxication parameters were observed during the sixth month of the study, which indicates the stability of the changes achieved during the first stage of treatment. The only exception was the sorption capacity of erythrocytes, which showed signs of normalization. A significant increase in endogenous intoxication due to the accumulation of metabolic products was found in the combination of type 2 diabetes mellitus with excretory pancreatic insufficiency. Additional use of the drug phenibut and acupressure courses led to a decrease in endogenous intoxication, which was more pronounced and persistent than in the subgroup with exclusively conventional treatment.